Institutionalizing environmental hazards for ‘public needs’: Destruction of forest for drinking water supply in Kerala, India - S. Mohammed Irshad
Natural resource exploitation is increasingly being considered as a technical issue with the assumption that it can be compensated for. The public concern shifts towards such destruction only when it affects the normal course of day to day life. Immediate needs often undermine the process of institutionalizing knowledge to ensure conservation of natural resources. The question of immediate needs often acts as the determining factor in decision making. This paper is focused on such an environmentally-legal issue in ensuring water availability through the destruction of rain forest. This paper discusses this issue in detail and raises the question of failure of institutionalizing knowledge.